Complete atrioventricuar block in children - B. Widhanarto; A. Samik; Saliki Saliki (Indonesian Pediatric Society, 1985)
Two cases (a 7 years and a 2 years old boy) suffering from complete atrioventricular block have been reported. Both of them were found accidentally without any subjective symptoms of atrioventricular block although the ventricular rate was lessÂ· than 45 times per minute. The diagnosis was easily established with eletrocardiographic examinations. It was necessary to detect the underlying diseases, and for this purpose some appropriate laboratory examinations were done. Rheumatic fever and viral myocarditis were suspected to be the underlying disease in these cases. The follow up during 7 years for the case with rheumatic fever and 3 months for the case with viral myocarditis showed that the abnormalities were permanent, and they did not require any specific treatment for the atrioventricular block itself.